2019
DOI: 10.1002/ece3.4893
|View full text |Cite
|
Sign up to set email alerts
|

Extensive secondary contact among three glacial lineages of Arctic Char (Salvelinus alpinus) in Labrador and Newfoundland

Abstract: Aim The Pleistocene glaciation event prompted the allopatric divergence of multiple glacial lineages of Arctic char ( Salvelinus alpinus ), some of which have come into secondary contact upon their recolonization of the Holarctic. While three glacial lineages (Arctic, Atlantic, and Acadian) are known to have recolonized the western Atlantic, the degree of overlap of these three lineages is largely unknown. We sought to determine the distribution of these three glacial li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 63 publications
4
33
0
Order By: Relevance
“…However, we cannot completely exclude the possibility that divergence occurred during a period of allopatry followed by secondary contact as similar contemporary patterns of genetic variation may be generated by alternative divergence histories (Foote, 2018;Ravinet et al, 2017). Indeed, studies of Arctic charr, and other northern fishes, have shown that allopatric divergence followed by a secondary contact event is prevalent (Jacobs et al, 2020;Lehnert et al, 2019;Rougemont & Bernatchez, 2018;Rougeux et al, 2019;Salisbury et al, 2019). Although unlikely due to geography, it is also possible that populations of Arctic charr from lakes not included in this study could have contributed to morph formation.…”
Section: Population Genetic Structure and Admixturementioning
confidence: 93%
“…However, we cannot completely exclude the possibility that divergence occurred during a period of allopatry followed by secondary contact as similar contemporary patterns of genetic variation may be generated by alternative divergence histories (Foote, 2018;Ravinet et al, 2017). Indeed, studies of Arctic charr, and other northern fishes, have shown that allopatric divergence followed by a secondary contact event is prevalent (Jacobs et al, 2020;Lehnert et al, 2019;Rougemont & Bernatchez, 2018;Rougeux et al, 2019;Salisbury et al, 2019). Although unlikely due to geography, it is also possible that populations of Arctic charr from lakes not included in this study could have contributed to morph formation.…”
Section: Population Genetic Structure and Admixturementioning
confidence: 93%
“…In North America, Arctic Char comprises four known mitochondrial DNA (mtDNA) lineages associated with distinct glacial refugia (Brunner et al, 2001;Moore et al, 2015). The Arctic lineage is predominant in the south-eastern Arctic (Brunner et al, 2001;Moore et al, 2015), but populations across northern Labrador are admixed with the Atlantic lineage (Salisbury et al, 2019). Nunavik, situated in northern Québec (Canada), is one of the last regions in North America to have deglaciated following the last glacial maximum (LGM; Dalton et al, 2020;Dyke, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In North America, Arctic Char comprises four known mitochondrial DNA (mtDNA) lineages associated with distinct glacial refugia (Brunner et al, 2001 ; Moore et al, 2015 ). The Arctic lineage is predominant in the south‐eastern Arctic (Brunner et al, 2001 ; Moore et al, 2015 ), but populations across northern Labrador are admixed with the Atlantic lineage (Salisbury et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In some species, resident populations are clearly genetically divergent from their diadromous counterparts (e.g., common galaxias; Delgado et al., 2019 ). In Arctic charr, sympatric anadromous and resident populations were until recently considered genetically indistinguishable, yet recent genomic data revealed genetically differentiated sympatric anadromous and resident populations in Labrador ( Salisbury et al, 2019 , 2020 ). Sockeye Salmon ( O. nerka ) on the other hand, exhibits examples of both genetically differentiated and non-differentiated sympatric resident and anadromous populations ( Nichols et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%